2015
DOI: 10.1155/2015/696372
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Probiotic Soymilk Fortified with Omega-3 on Blood Glucose, Lipid Profile, Haematological and Oxidative Stress, and Inflammatory Parameters in Streptozotocin Nicotinamide-Induced Diabetic Rats

Abstract: Objective. The aim of the present study was to evaluate the effects of probiotic soymilk fortified with omega-3 in diabetic rats. Methods. Soymilk (SM), fermented soymilk (FSM), and fermented soymilk fortified with omega-3 (FSM + omega-3) were prepared. Rats were randomly assigned to five groups of 13 animals per group. Diabetes was induced by a single injection of streptozotocin (STZ) 15 min after the intraperitoneal administration of nicotinamide (NA). Normal control (NC) and diabetic control (DC) rats recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Lin et al (2005) reported that the intake of fermented soymilk lowered total cholesterol and triglyceride accumulation in the liver under the CCl 4 ‐induced oxidative stress rat model. Likewise, Mohammadi Sartang et al (2015) also reported the decreased concentrations of total cholesterol and triacylglyceride, and increased concentrations of HDL in fermented soymilk supplemented groups compared to the diabetic control group. The presence of n‐3 fatty acids and aglycone isoflavones in fermented soymilk could explain the aforementioned phenomena.…”
Section: Health Benefits Of Soymilk Fermented By Labmentioning
confidence: 86%
“…Lin et al (2005) reported that the intake of fermented soymilk lowered total cholesterol and triglyceride accumulation in the liver under the CCl 4 ‐induced oxidative stress rat model. Likewise, Mohammadi Sartang et al (2015) also reported the decreased concentrations of total cholesterol and triacylglyceride, and increased concentrations of HDL in fermented soymilk supplemented groups compared to the diabetic control group. The presence of n‐3 fatty acids and aglycone isoflavones in fermented soymilk could explain the aforementioned phenomena.…”
Section: Health Benefits Of Soymilk Fermented By Labmentioning
confidence: 86%
“…For example, soy yogurt, produced by bacterial fermentation of soy milk, has attracted attention in the plant-based yogurt alternatives market due to its unique nutritional values [ 7 ]. Recently, it has been reported that soy yogurt showed health benefits related to high antioxidant activity, reduction in the risk of diabetic diseases, and prevention against chronic inflammation [ 8 , 9 , 10 ]. However, the manufacture of soy yogurt remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…85‐23 principles (NIH Publication Revised, 1985), and ethical approval was obtained from the Institute of Public Health, Obafemi Awolowo University, Ile‐Ife, Nigeria, with approval number IPH/OAU/12/1263. The experimental rats were fasted without food after acclimatization but had access to water for 12 h. The fasting blood glucose level was determined in the blood drawn from the retro‐orbital plexus of the animals using fine‐test glucometer as described by Mohammadi Sartang, et al [ 35 ]…”
Section: Methodsmentioning
confidence: 99%